PENERAPAN NILAI-NILAI REVOLUSI MENTAL APARATUR SIPIL NEGARA DI BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN MINAHASA UTARA - TANASELA, FRISCA MARSELA; Lengkong, Daicy Florence; Tulusan, Femmy (Sam Ratulangi University, 2016)
Abstract : The implementation of mental revolution vale is a mind program from president of republic Indonesia. But the implementation of the program is not run snoothly at this moment cause there are many problems happend in the implementation of mental revolution such as beliefeness, hope, compasionate, and civil cocupation as a subjec.This research uses qualitative research methods. Informant research by as much as 10 (ten) the informant i.e. consists of 1 head of the Agency, 1 Secretary, 1 head of the Agency, then 2 officers and 2 community. Data collection techniques used i.e., interview techniques, techniques of observation/observation, and technical documentation. As well as the Data analysis techniques used for Data Reduction, namely, The Presentation of Data, as well as the withdrawal of conclusions based on research conducted the nation's Unity in the body of researchers and politics of North Minahasa Regency researched through observation, reality as well as data or documents such as the report of the performance government agencies, strategic plan, a long-term plan. The conclusion can be drawn in the research in the body of the unity of the nation and the Politics of North Minahasa Regency in implementing a Mental revolution of values through 4 Filosofi basic Mental Revolution values as follows:Keyword : The values of the revolution mental, Civil State Apparatus